Coeliac disease in the Rehovot-Ashdod region of Israel: incidence and ethnic distribution. Issue 1 (March 1984) - Dahan, S; Slater, P E; Cooper, M; Brautbar, C; Ashkenazi, A
Abstract : The data from a large group of children with biopsy proved coeliac disease born in the Rehovot-Ashdod region of Israel and treated in a regional hospital provided us with the basis for the determination of the annual birth cohort incidence of coeliac disease for the period 1968-81. The findings show a minimum birth cohort incidence of 1.71/1000 live births. The highest incidence rate was in children of Asian origin and the lowest in second generation Israel born. The incidence of coeliac disease rose sharply during the study period.